Comparative analysis of properties of working fluids of power installations based on extended thermodynamic similarity. Issue 3 (December 2020) - Chirkov, A Yu; Lola, D E; Luo, T; Boronovskiy, E G
Abstract: The influence of the thermophysical properties of the working fluid on the efficiency of the working cycle is considered. Using methods of thermodynamic similarity, it is shown that one of the important factors affecting the efficiency of the thermodynamic cycle is the ratio between the slope of the saturated vapor line in the entropy–temperature diagram and the slope of vapor isobars. The influence of the composition of the working fluid and the ability to control it for maximum efficiency is discussed.